2003
DOI: 10.1017/s0074180900210899
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium Chemistry in the Atmospheres of Brown Dwarfs

Abstract: Abstract. Carbon monoxide and ammonia have been detected in the spectrum of GI 229B at abundances that differ substantially from those obtained from chemical equilibrium. Vertical mixing in the atmosphere is a mechanism that can drive slowly reacting species out of chemical equilibrium. We explore the effects of vertical mixing as a function of mixing efficiency and effective temperature on the chemical abundances in the atmospheres of brown dwarfs and on their spectra. The models compare favorably with the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 20 publications
(37 reference statements)
2
52
0
Order By: Relevance
“…This same effect has now been observed in brown dwarf Mband photometry (Golimowski et al, 2004), as anticipated by Fegley & Lodders (1996). This excess CO leads to strong absorption at 4.5 µm, leading to diminished flux in M-band (Saumon et al, 2003). Consequently, when searching for giant planets, L-band may be just as favorable as M-band.…”
Section: Other Detectability Issuessupporting
confidence: 75%
See 1 more Smart Citation
“…This same effect has now been observed in brown dwarf Mband photometry (Golimowski et al, 2004), as anticipated by Fegley & Lodders (1996). This excess CO leads to strong absorption at 4.5 µm, leading to diminished flux in M-band (Saumon et al, 2003). Consequently, when searching for giant planets, L-band may be just as favorable as M-band.…”
Section: Other Detectability Issuessupporting
confidence: 75%
“…We use the elemental abundance data of Lodders (2003) and compute chemical equilibrium compositions following Fegley & Lodders (1994) and Lodders & Fegley (2002). In addition, we maintain a large and constantly updated opacity database.…”
Section: Atmosphere Modelsmentioning
confidence: 99%
“…The lithium abundance has been reduced by a factor 1000 in the T eff = 1300 K model in order to provide a meaningful upper limit to the observed levels of Li i absorption in the spectrum of ε Indi Ba. Griffith & Yelle (1999) and Saumon et al (2003) have shown that this excess can be explained by the upmixing of CO from the warm deeper layers, since if one assumes sufficiently efficient turbulent mixing in the upper atmosphere, the kinetic rates for the conversion reactions from CO to CH 4 are too slow to adjust the mixing ratios to CE abundances. The BT-Settl models employ a similar calculation of these CE departure effects, but using diffusion coefficients derived from the CO5BOLD radiation hydrodynamics simulations (Freytag et al 2010) rather than adjusting them as a free parameter (Homeier et al, in prep.).…”
Section: Chemical Equilibrium Departuresmentioning
confidence: 99%
“…between 1000 and 1500 K, the diffusion coefficient in this part of the overshoot region would best characterise our model, corresponding to 10 7 −10 8 cm 2 /s in the ε Indi Ba model. In addition, we consider several reaction pathways and timescales besides the one from Prinn & Barshay (1977), on which the Saumon et al (2003) models are based, notably the revised time scale for the scheme of Prinn & Barshay (1977) suggested by Griffith & Yelle (1999), and the reaction scheme of Yung et al (1988) (see also Griffith & Yelle 1999). Among these, the Yung et al (1988) model generally predicts the fastest conversion rates from CO to CH 4 , and the Prinn & Barshay (1977) model with the modified rates of Griffith & Yelle (1999) the slowest rates, implying the strongest CE departure effects.…”
Section: Chemical Equilibrium Departuresmentioning
confidence: 99%
“…A non-equilibrium correction to the equilibrium abundances of CH 4 /CO and NH 3 /N 2 due to vertical mixing (Saumon et al 2003) has been adopted to explain the observations of these species in brown dwarfs. A similar nonequilibrium treatement is used by Barman et al (2011a) to model the exoplanet HR8799b.…”
Section: Departures From Equilibriummentioning
confidence: 99%